2017
DOI: 10.1002/prp2.340
|View full text |Cite
|
Sign up to set email alerts
|

A novel free fatty acid receptor 1 (GPR40/FFAR1) agonist, MR1704, enhances glucose‐dependent insulin secretion and improves glucose homeostasis in rats

Abstract: Activation of G protein‐coupled receptor 40/Free fatty acid receptor 1 (GPR40/FFAR1), which is highly expressed in pancreatic β cells, is considered an important pharmacologic target for the treatment of type 2 diabetes mellitus. The aim of this study was to determine the effect of MR1704, a novel GPR40/FFAR1 agonist, on glucose homeostasis in rats. MR1704 is a highly potent and selective, orally bioavailable agonist with similar in vitro potencies among humans, mice, and rats. Treatment of rat islets with MR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…It has been found that the activation of FFAR1 ameliorates the fasting hyperglycemia and glucose tolerance in diabetic rats [ 24 ]. More importantly, no hypoglycemic effects and pancreatic toxicity were observed in normal rats, suggesting selective beneficial effects for type-2 diabetes patients [ 24 , 25 ]. GK, primarily expressed in pancreatic β-cells and liver hepatocytes, is known to play a crucial role in glucose homeostasis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the activation of FFAR1 ameliorates the fasting hyperglycemia and glucose tolerance in diabetic rats [ 24 ]. More importantly, no hypoglycemic effects and pancreatic toxicity were observed in normal rats, suggesting selective beneficial effects for type-2 diabetes patients [ 24 , 25 ]. GK, primarily expressed in pancreatic β-cells and liver hepatocytes, is known to play a crucial role in glucose homeostasis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the NADPH oxidase complex generates ROS that may act as second messengers for GSIS [29,30,37]. In addition, GPR40 activation by FFAs or by agonist molecules also leads to the generation of additional second messengers such as DAG, Ca 2+ and cAMP, also culminating in the enhancement of insulin secretion [1,[6][7][8]38,39].…”
Section: Discussionmentioning
confidence: 99%
“…MR1704, a GPR40/FFAR1 agonist, exhibits favorable pharmacokinetic profiles and improves glucose homeostasis without the risk of hypoglycemia, pancreatic toxicity, or pancreatic b‐cell exhaustion (Tsuda et al, ). In the present study, we examined the effect of MR1704 in rats unresponsive to glibenclamide and determined the risk of secondary failure in ZF rats.…”
Section: Discussionmentioning
confidence: 99%
“…MR1704 is a highly potent, selective, orally bioavailable GPR40/FFAR1 agonist, which exhibited favorable pharmacokinetic profiles and pharmacological effects in several animal models, without causing hypoglycemia (Tsuda et al, ). Chronic treatment with MR1704 for 5 weeks decreased the glycated hemoglobin levels in Goto–Kakizaki rats, and its glucose‐lowering effect persisted during the study period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation